Medicina veterinária integrativa no tratamento da dermatite atópica canina (DAC): acupuntura, ozonioterapia, homeopatia e fitoterapia - Rodrigues, Camila Percário (Universidade Estadual Paulista (Unesp), 2022)
Canine Atopic Dermatitis (CAD) is characterized as a pruritic, chronic and inflammatory disease, affecting mainly animals between 6 months and 3 years of age. The origin of the disease is linked to several factors, including the existence of a deficient epidermal barrier, cutaneous dysbiosis, allergic sensitization, immune dysregulation and production of immunoglobulin-E against environmental and food allergens. The diagnosis of CAD is complex, since there are no routine complementary exams in the practice of small animal clinics. Thus, the clinical signs, the animal's history and the discard of similar diseases support the initial diagnostic suspicion. The treatment of CAD is multimodal, using techniques and administration routes to better restore the animal's health. The disease can vary between the acute or chronic form, and treatments are specific for each phase. Due to the difficult treatment, many animals use medications for a long time, e.g., glucocorticoids, aiming at controlling the allergic and pruritic condition. However, the continuous use of these drugs can predispose the animal to adverse reactions and a worsening of the quality of life. In this context, integrative medicine stands out as promising alternative treatments for diseases without the prolonged use of drugs, aiming at a better quality of life for animals. In this scenario, the present study reviewed aspects of CAD and integrative veterinary medicine, with an emphasis on the use of acupuncture, ozone therapy, homeopathy and phytotherapy in the condition

A Dermatite Atópica Canina (DAC) é caracterizada como doença pruriginosa, crônica e inflamatória, acometendo animais principalmente entre 6 meses e 3 anos de idade. A origem da doença está ligada a vários fatores, incluindo à existência de barreira epidérmica deficitária, disbiose cutânea, sensibilização alérgica, desregulação imunológica e produção de imunoglobulina-E contra alérgenos ambientais e alimentares. O diagnóstico da DAC é complexo, uma vez que não existem exames complementares de rotina na prática da clínica de pequenos animais. Assim os sinais clínicos, histórico do animal e descarte de doenças semelhantes embasam a suspeita diagnóstica inicial. O tratamento da DAC é multimodal, utilizando técnicas e vias de administração para melhor restabelecimento da saúde do animal. A doença pode variar entre a forma aguda ou crônica, e os tratamentos são específicos para cada fase. Devido ao difícil tratamento muitos animais utilizam medicamentos de modo prolongado, e.g., glicocorticóides, visando o controle do quadro alérgico e pruriginoso. No entanto, o uso contínuo destes fármacos pode predispor o animal a reações adversas e uma piora da qualidade de vida. Neste contexto, a medicina integrativa desponta como promissora para tratamentos alternativos de doenças sem o uso prolongado de fármacos, visando maior qualidade de vida dos animais. Neste cenário, o presente estudo revisou aspectos da DAC e da medicina veterinária integrativa, com ênfase no uso da acupuntura, ozonioterapia, homeopatia e fitoterapia na afecção.
Integrative veterinary medicine in the treatment of Canine Atopic Dermatitis (CAD): acupuncture, ozone therapy, homeopathy and phytotherapy
Keywords: Atopy in dogs; Allergopathies; Complementary veterinary medicine; Atopia em cães; Alergopatias; Medicina veterinária complementar